Meta-Analisis Pengembangan Media Pembelajaran Kimia SMA Berbasis Android - Mangido Sitorus; Abdul Hadjranul Fatah; I Made Sadiana; Nopriawan Berkat Asi; Anggi Ristiyana Puspita Sari (FKIP Universitas Palangka Raya, 2022)
This study aims to describe the suitability of learning objectives for the pretest and posttest questions, the syntax of the media development model, and chemistry learning materials for the learning syllabus. This study used qualitative meta-analysis research. The object of this research was taken from one thesis of the UNY chemistry education study program and two UPR thesis with the theme Development of android-based chemistry learning media. Data collection techniques in study used documentation techniques from learning objective documents, media development model syntax, learning materials, media expert and material expert assessment results sheets, pretest-posttest and learning outcomes. The results of the research show that media development model used by each thesis still has discrepancy with the theoretical syntax of the media development model. The purpose of learning with the application of the Bohr and Gall development model is discrepancy with the pretest-posttest. The learning objective of the thesis is to apply the DDD-E development model, a discrepancy in pretest-posttest with a N-gain of 0.43 (Medium). The learning objectives in application of the DDD-E development model were categorized according to the pretest-posttest questions with a N-gain of 0.71 (High), with the application of the media development model being categorized as appropriate.